The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1037/aap0000024
|View full text |Cite
|
Sign up to set email alerts
|

The sociocultural context of caregiving experiences for Vietnamese dementia family caregivers.

Abstract: The goal of this qualitative study was to describe the beliefs and experiences of Vietnamese caregivers caring for a family member with dementia and to elicit their ideas about promising interventions. We recruited 10 caregivers from support groups, the Alzheimer’s Association, and local community-based organizations in Northern California. We conducted semi-structured in-depth interviews with all caregivers, as well as a focus group to obtain ideas about supportive strategies. Several themes emerged from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 37 publications
(63 reference statements)
7
71
0
3
Order By: Relevance
“…They identified that the patients' families are responsible for: feeding (including through a nasogastric tube), administering medications, cleaning the patient, making beds, repositioning, taking swabs, giving oxygen and urinary catheter care, etc. Similar involvement of patients' family caregivers in the direct care has also been reported from Vietnam, 11 Korea, 6,22,23 India, 12 Indonesia, 5,18,24 and China. 9,10,14,15 The concern here is that these patient care activities are no different from the care activities that are associated with the contamination of health care workers (HCW) hands during the patient care.…”
supporting
confidence: 75%
“…They identified that the patients' families are responsible for: feeding (including through a nasogastric tube), administering medications, cleaning the patient, making beds, repositioning, taking swabs, giving oxygen and urinary catheter care, etc. Similar involvement of patients' family caregivers in the direct care has also been reported from Vietnam, 11 Korea, 6,22,23 India, 12 Indonesia, 5,18,24 and China. 9,10,14,15 The concern here is that these patient care activities are no different from the care activities that are associated with the contamination of health care workers (HCW) hands during the patient care.…”
supporting
confidence: 75%
“…Topics: experiences and discussion focused on each identified unmet needs or challenges. 2014/ Germany [90]Muders et al85 CGsQuestionnaire with two open-ended questions. Topics: exploration and documentation of the CG’s needs and identification of the healthcare professionals to adequately support them. 2015/ USA [91]Meyer et alTen vietnamese informal CGs; seven female; two spouse; mean age = 55Semi-structured interviews ( n  = 10 CGs). Topics: family structure and immigration, beliefs about dementia, experiences with caregiving, coping strategies, help-seeking and service utilization.1 Focus group ( n  = 5 CGs).…”
Section: Resultsmentioning
confidence: 99%
“…El nivel educativo del cuidador varía en las diferentes investigaciones. Así mismo, en ninguna de las investigaciones revisadas se tiene en cuenta el número de integrantes en la familia (Aparicio et al, 2008;Ascher et al, 2010;Ávila, García & Gaitán, 2015;Ayuso et al, 2007;Butman et al, 2003;Calero, Fernández & Roa, 2009;Celdrán, Triadó & Villar, 2009;Cerquera & Galvis, 2013;Espín, 2012;Glynn, Hahn, Hayden, Randall & Randolph, 2012;Kim, 2012;Krikorian, Velez, González, Palacio & Vargas, 2010;Losada, Márquez, Puente, Gallagher, & Knight, 2007;Mausbach, Chattillion & Ziegler, 2012;Mausbach et al, 2014;Meyer, Nguyen, Dao, & Arean, 2015;Mioshi, Bristow, Cook & Hodges, 2009;Moreno, 2008;Pabón, Galvis & Cerquera, 2014;Palacio, 2012;Valero & Cruz, 2013;Razani, 2007;Riedjik, 2006;Rodríguez, 2013;Vargas & Pinto, 2010) En cuanto a elementos relacionales (ver Figura 3) se identificó que, para ser considerado cuidador principal, debe cumplir con un tiempo mínimo de 3 meses como cuidador y conviviendo con la persona. En términos de ubicación en la red, es común que el cuidador sea el cónyugue y/o hijo, en menor porcentaje se trata de personas con menor grado de consanguinidad y en su gran mayoría no se evidencia apoyo al cuidador por parte de redes informales o formales (Aparicio et al, 2008;Ávila et al, 2015;Ayuso et al, 2007;Butman et al, 2003;Calero et al, 2009;...…”
Section: Figura 2 Resultado Por Características De La Redunclassified